Opportunity Evaluation under Risky Conditions: The Cognitive Processes of Entrepreneurs - Keh, Hean Tat; Der Foo, Maw; Lim, Boon Chong (Entrepreneurship Theory and Practice, 2002)
Even though the entrepreneurship literature places much emphasis on opportunity recognition, little is known about how entrepreneurs actually evaluate opportunities. This study uses a cognitive approach to examine opportunity evaluation, as the perception of opportunity is essentially a cognitive phenomenon. We present a model that consists of four independent variables (overconfidence, belief in the law of small numbers, planning fallacy, and illusion of control), a mediating variable (risk perception), two control variables (demographics and risk propensity), and the dependent variable (opportunity evaluation). We find that illusion of control and belief in the law of small numbers are related to how entrepreneurs evaluate opportunities. Our results also indicate that risk perception mediates opportunity evaluation.